2021
DOI: 10.1038/s41598-021-97287-3
|View full text |Cite
|
Sign up to set email alerts
|

Development of an efficient gene-targeting system for elucidating infection mechanisms of the fungal pathogen Trichosporon asahii

Abstract: Trichosporon asahii is a pathogenic fungus that causes severe, deep-seated fungal infections in neutropenic patients. Elucidating the infection mechanisms of T. asahii based on genetic studies requires a specific gene-targeting system. Here, we established an efficient gene-targeting system in a highly pathogenic T. asahii strain identified using the silkworm infection model. By comparing the pathogenicity of T. asahii clinical isolates in a silkworm infection model, T. asahii MPU129 was identified as a highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(42 citation statements)
references
References 41 publications
1
40
0
Order By: Relevance
“…The ku70 gene-deficient strain of the T. asahii MPU129 strain has high homologous recombination efficiency, making it useful as a parent strain 28 . Using this strain, we generated the cna1 gene-deficient mutant.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The ku70 gene-deficient strain of the T. asahii MPU129 strain has high homologous recombination efficiency, making it useful as a parent strain 28 . Using this strain, we generated the cna1 gene-deficient mutant.…”
Section: Resultsmentioning
confidence: 99%
“…The T. asahii strain (MPU129 ku70 gene-deficient mutant) used in this study was generated as previously reported 28 . The T. asahii MPU129 ku70 gene-deficient mutant was grown on Sabouraud dextrose agar (SDA) (1% hipolypepton [Nihon Pharmaceutical Co., Ltd., Tokyo, Japan], 4% dextrose, and 1.5% agar [both from FUJIFILM Wako Pure Chemical Industries, Osaka, Japan]) containing G418 (50 μg/ml) and incubated at 27 °C for 2 days.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Phenotypic analyses using gene-deficient mutants are important for clarifying the molecular mechanisms of infection and drug resistance in T. asahii. We established a method for generating a gene-deficient mutant of T. asahii using an Agrobacterium tumefaciens-mediated gene transfer system (Matsumoto et al 2021). The efficiency of genetic recombination in T. asahii was increased by deleting the ku70 gene that encodes the Ku70 protein, a subunit of the non-homologous end-joining repair enzyme (Matsumoto et al 2021).…”
Section: Introductionmentioning
confidence: 99%